The Use of Extended Reality Technologies in Sport Perceptual-Cognitive Skill Research: A Systematic Scoping Review - Aden Kittel; Riki Lindsay; Peter Le Noury; Luke Wilkins (Sports Medicine - Open)
Abstract Background Extended Reality (XR) technologies, such as Virtual Reality (VR) and 360°VR are growing rapidly in the scientific literature and sporting practice. These have been used for a range of skills, particularly perceptual-cognitive skills. However, to our knowledge, there is no systematic scoping review on this topic identifying the current state of play of the research area by characteristics such as study type, technology type, or sport investigated, and such a review would help guide the future direction of this area. Therefore, this study aimed to systematically review the extent of XR technology in sport for assessing and training athletes’ and officials’ perceptual-cognitive skills. Methods Electronic databases (SCOPUS, Web of Science, SPORTDiscus, PsycINFO) were searched for relevant articles up until January 2024. Studies were included if they used XR technologies to assess or develop sport-specific, higher order perceptual-cognitive skills. Results 57 studies met the inclusion criteria for this review, of which 67% were published from 2020. Most studies conducted quantitative research designs, with 66% of studies adopting a cross-sectional assessment approach and 28% conducting an intervention to assess performance improvements. Decision-making was the most prevalent skill investigated, across 60% of studies. The most common technology was head mounted display (51%) presenting animated environments and the most common sports investigated were football and handball (32% and 19% of studies, respectively). Conclusions This review highlights a significant growth in the research exploring XR technologies in sport for perceptual-cognitive skill development and understanding, with most studies published in the last 4 years. Prominent technology types (e.g. animated HMD), perceptual-cognitive skills (e.g. decision making), study designs (e.g. quantitative assessment), and sports (e.g. football) are identified and discussed along with practical implications and future research. Key Points Extended reality technologies for sports perceptual-cognitive skills is an emerging field, marked by key trends in the types of technology used and the perceptual-cognitive skills being studied. Decision-making is the most commonly studied perceptual-cognitive skill, and these technologies report to have high representativeness and engagement when being used. More research is required to explore the effectiveness of this technology through intervention study designs, and further understand how it can be used and the perceptual-cognitive processes through qualitative research designs.